The American short story cycle - Smith, Jennifer J. (Jennifer Joan) (Edinburgh University Press Ltd, 2018)
This work spans two centuries to tell the history of a genre that includes both major and marginal authors, from Washington Irving through William Faulkner to Jhumpa Lahiri.